PENDIDIKAN ISLAM DI TENGAH TANTANGAN GLOBALISASI - Zainal Azman (El-Ghiroh : Jurnal Studi Keislaman, 2017)
Globalization is an entity, however small, that when where delivered by anyone, anywhere, and anytime, will rapidly spread throughout the globe. If the entity which had already become a lifestyle and a symbol of modernity, it can change a person's habits, in fact rarely assess religious teachings as obsolete. If Islamic education does not do anything in the face of sophisticated and modern technology, it can be ascertained that the Muslims would be a passive spectator and not a player, or as consumers, not producers. Thus, attempts to reformat the theory and practice of Islamic education, can not, it must be done, by revamping insight and mindset: act locally, think globally.